Feasibility and effectiveness of telemedicine for adult patients with congenital heart disease: A one-year single-center experience-based studySummary table - Nunzia Borrelli; Nicola Grimaldi; Flavia Fusco; Antonio Orlando; Michela Palma; Maria Cristina Boccia; Sabrina Bassolino; Anna Iervolino; Berardo Sarubbi (International Journal of Cardiology Congenital Heart Disease)
Introduction: The number of adults with congenital heart disease has significantly increased in recent years. While telemedicine has emerged as a promising approach to improve care delivery and patient outcomes, its use for adults with congenital cardiopathies has not been extensively explored. This study aims to evaluate the feasibility and clinical impact of a telemedicine programme for adults with congenital heart diseases. Methods: This was a single-center, prospective, observational study, carried out between January 2022 and January 2023. A wristwatch, a paired mobile device, and a dedicated hospital workstation were used to telemonitor 25 adult patients with moderate-to-severe congenital heart condition, in II-IV New-York Heart Association class. We assessed changes in hospital admission days and related costs, patient satisfaction, and functional parameters, including 6-min walk test distance, vital signs, and echocardiographic ejection fraction. Results: All 25 patients agreed to participate to the telemedicine program (mean age 38.35 ± 11.33 years, 52 % male). Twenty-three patients completed the program. No significant changes were observed in vital signs, functional class, ventricular ejection fraction, while walking distance significantly improved (404 ± 82 m versus 433 ± 142 m, p = 0.03). Notably, hospital admission days and related costs were significantly reduced during the TM program year compared to the prior year. Patient satisfaction was high. One patient experienced a prolonged hospitalization and death due to the natural progression of their condition. Conclusion: High-risk patients with moderate-severe congenital heart disease can benefit from a device-implemented telemedicine program, which offers tailored, specialized care directly at home, reducing hospital admissions and ensuring stable clinical status.